2016 IEEE 36th International Conference on Distributed Computing Systems (ICDCS) 2016
DOI: 10.1109/icdcs.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

ChitChat: An Effective Message Delivery Method in Sparse Pocket-Switched Networks

Abstract: The ubiquitous adoption of portable smart devices has enabled a new way of communication via Pocket Switched Networks (PSN), whereby messages are routed by personal devices inside the pockets of ever-moving people. PSNs provide opportunities for various interesting applications such as locationbased social networking, geolocal advertising, and military missions in active battlefields where the central communication tower is unavailable. One key challenge of the successful roll-out of PSN applications is the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…ChitChat [19] is one of those message delivery methods where routing decisions are made based on the higher probability that the message receiver has of relaying it to the next node closer to the destination or that have high chance of forwarding it to the destination. This method approaches to make message delivery possible in such situations where there is no fixed connection between dynamic nodes.…”
Section: Chitchatmentioning
confidence: 99%
See 2 more Smart Citations
“…ChitChat [19] is one of those message delivery methods where routing decisions are made based on the higher probability that the message receiver has of relaying it to the next node closer to the destination or that have high chance of forwarding it to the destination. This method approaches to make message delivery possible in such situations where there is no fixed connection between dynamic nodes.…”
Section: Chitchatmentioning
confidence: 99%
“…It has shown some results regarding having more hop counts than Sane [20] and Sedum [21] but has indicated that lower hop count does not ensure efficiency but portrays capability to deliver message to neighboring nodes while failing to deliver most of the created messages. In addition to that ChitChat [19] has shorter buffer as it makes intelligent decisions in forwarding Messages other than flooding and filling up the buffer unnecessarily without creating network congestion. The following pseudocode [19] represents the Real-time transient social relationship modeling.…”
Section: Chitchatmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some relevant research has been conducted on the data dissemination in MONs. Mcgeehan et al propose a message routing approach ChitChat [6], which exploits users' direct and transient social interests via discriminatory gossiping to penetrate messages deeper into the network. ChitChat enables message carriers to make opportunistic and distributed routing decisions based on the likelihood of forwarding the messages to the destination.…”
Section: Related Workmentioning
confidence: 99%
“…Fig. 1 represents such a network where people share their messages until the connection lasts among the mobile phones within certain regions when they move around [18][19][20][21]. In relation to such concept, cluster detection methods have been used to ensure effective message delivery in such networks.…”
Section: Introductionmentioning
confidence: 99%